Comparative study on Islamic banking and conventional banking performance in Malaysia - Marcus, Catherine (2020)
Conventional banks and Islamic banks are commonly distinguished on the basis of their goals, 'riba' and risk-sharing practices, as well as their financial products and performances. The primary objective of this study is to determine the financial performance of Islamic banks and non-Islamic banks in Malaysia, using a financial ratio from 2011 to 2015. The specific objective of this study is to empirically analyst the profitability performance, liquidity performance and credit risk performance of both Islamic banks and non-Islamic banks. A comparative performance evaluation was considered between Islamic banking (IB) and conventional banking (CB), in the context of Malaysia. This study is useful for depositors, bank managers, shareholders, investors, regulators and academic researchers in order to offer a clear picture and references of the financial conditions during the period considered. The performance of Islamic and Conventional banks is examined through the calculation of financial ratios, return on assets and equity, where six financial ratios represented the independent variables (IV), and return on assets (ROA) and equity (ROE) represented the dependent variables (DV). Ten conventional banks and ten Islamic banks were sampled with the data generated from their respective annual financial cash flow statements extracted from their official bank's websites, and from Bank Negara Malaysia (BNM). Data was generated from the audited financial statements during the 2011-2015 period, income statements, balance sheets as well as the cash flow statements for each Islamic and conventional bank. The significance of the data was determined using an independent sample t-test and regression analysis. According to the analysis, the researcher concluded that Islamic banks are less profitable, less liquid and more risky, but at the same time more efficient in managing the operating expenses to generate revenue, as compared conventional banks. For future research, the sample size should be increased for the same study, and more banks should be taken as an example to generalize the results of the study to the entire industry.